Drinking in the North of European Russia: From Traditional to Totalising Liminality - Andrei V. Tutorsky (Journal of Ethnology and Folkloristics)
This article explores the topic of alcohol consumption in Russia. My fieldwork was conducted in the north of European Russia between 2010 and 2014 in Arkhangelskaya and Vologodskaya oblasts. The main idea of the paper is to look at alcohol drinking through the lens of rites of passage and especially liminality. I argue that the traditional festivities, and alcohol consumption with the traditional type of liminality, were based on a small amount of sugar and money and also the long period of time required to make beer. In 1960s, after ukrupneniye and the urbanisation of villages, money and spirits came to the villages. Together with an existing prohibition on ceremonies and rites they created a new permanent liminality of drinking. This new liminality included getting dead drunk and was paradoxically approved by Soviet ideology.